Civil Society and COVID in China: Responses in an Authoritarian Society. (December 2020) - Hu, Ming; Sidel, Mark
Can civil society play a useful role in response to a pandemic like COVID-19 in a one-party state? We explore that issue based on the role of civil society and philanthropy in responding to COVID in China, where a large and innovative—and restricted—civil society and philanthropy sector has developed. Our preliminary findings are that while restrictive policies toward civil society significantly limit the role that civil society organizations and philanthropy can have in response to the pandemic, civil society still shows strength and vitality in emergency service, funding, volunteering, mutual aid, in-kind donations, and even policy advocacy. While the prospects for civil society in China are uncertain because of political restrictions before and during the COVID crisis, civil society continues to build capacity and show its capabilities to Chinese citizens and its governance institutions.